Placing Colonial Ornithology: Imperial Ambiguities in Upper Canada, 1791- 1841 - Greer, Kirsten (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2008)
AbstractThis paper examines the emergence of colonial ornithology in Upper Canada, 1791-1841, to determine the impact of empire and local contexts on the natural history activity. I argue that colonial ornithology emerged as a by-product of British imperialism that helped to reinforce British, upper- and middle-class, gender-specific white identities through practices of sportsman-hunting, taxidermy, natural theology, and the romantic-aesthetic. However, as this paper reveals, British imperial practices and ideas of ornithology relied on the participation of First Nations and Métis peoples, whose knowledge and skills were instrumental to British naturalists. The First Nations and Métis peoples therefore exerted a real presence in colonial ornithology in Upper Canada—albeit a subservient one in the British ornithological texts—as they positioned themselves as part of the ornithological trade with the collection and trading of specimens. Furthermore, British military officers, settlers, and tourists tapped into American scientific networks and knowledge systems rather than focusing solely on Britain as an imperial centre of accumulation. British imperial ideas and practices of colonial ornithology in Upper Canada therefore remained ambiguous during the early nineteenth century.